THEORETICAL ASPECTS OF THE PROBLEM OF PREPARATION OF FUTURE PUPILS FOR THE DEVELOPMENT OF GOAL SETTING IN CHILDREN OF SENIOR PRESCHOOL AGE (Pedagogy of Higher and Secondary Education, 2022)
No abstract.